The Effect of Leadership on Performance of Apparatus and Institutions in Cimerang Village, Purabaya District, Sukabumi - Pambreni, Yuni; Rachmawati, Dwi; Hidayat, Rohmat (Neo Journal of economy and social humanities, 2022)
Leadership aims to encourage work passion, and high productivity and work productivity of employees, in order to achieve maximum organizational goals. In achieving goals, a leader is needed who can mobilize and influence his work group by paying attention to the desires of his subordinates. The purpose of this study was to determine the leadership, to find out the performance of employees and to determine the effect of leadership on employee performance at the Cimerang village office, Purwakarta sub-district, Sukabumi district. The research method used is descriptive and descriptive methods with a quantitative approach. In this study using primary data by observing and distributing questionnaires to respondents. The sampling technique used in this study was non-propability sampling with saturated sampling. The sample used in this study amounted to 30 employees. The correlation value of the influence of leadership (X) on the performance of the village apparatus (Y) is 22 indicators. The results of this study indicate that there is a significant influence of leadership influence on employee performance in Cimerang Village, Purabaya District, Sukabumi Regency.